2012
DOI: 10.1111/j.1538-7836.2012.04716.x
|View full text |Cite
|
Sign up to set email alerts
|

Diannexin, an annexin A5 homodimer, binds phosphatidylserine with high affinity and is a potent inhibitor of platelet‐mediated events during thrombus formation

Abstract: Summary. Background:  Shielding of procoagulant phosphatidylserine (PS) with annexin A5 attenuates thrombosis, but annexin A5 (35.7 kDa) is rapidly cleared from the circulation. In contrast, Diannexin, a 73.1 kDa homodimer of annexin A5, has an extended half‐life. Objectives:  To quantify the affinity of Diannexin for PS, examine its interaction with activated platelets and determine its effects on platelet‐mediated events during thrombus formation. Methods:  The affinities of Diannexin and annexin A5 for PS‐c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 50 publications
4
33
0
Order By: Relevance
“…This finding provides further validation for this highspeed, 2-color microscopy method for evaluating the effects of inhibitors on the markers of platelet activation in vivo. 24 The observation that atorvastatin delayed CD41 upregulation in eNOS-deficient mice, despite the fact that it only inhibited thrombin-and GYP-induced platelet activation, is consistent with previous observations that platelet activation in the laserinduced arteriolar model is thrombin dependent. 41,42 In conclusion, we have extended our understanding of how statins inhibit platelet activation.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This finding provides further validation for this highspeed, 2-color microscopy method for evaluating the effects of inhibitors on the markers of platelet activation in vivo. 24 The observation that atorvastatin delayed CD41 upregulation in eNOS-deficient mice, despite the fact that it only inhibited thrombin-and GYP-induced platelet activation, is consistent with previous observations that platelet activation in the laserinduced arteriolar model is thrombin dependent. 41,42 In conclusion, we have extended our understanding of how statins inhibit platelet activation.…”
Section: Discussionsupporting
confidence: 90%
“…24 Using the jugular vein cannulus, mice were given an infusion of 0.1 µg/g X488. Where indicated, an infusion of 1.3 µg/g of DyLight-647-tagged F ab fragments of rat anti-mouse CD41 (MWREG30, Emfret Analytics), a monoclonal antibody directed against α IIb that recognizes both the resting and activated form of this platelet-specific integrin, or 2 µg/g of DyLight-647-tagged antibody against P-selectin (RB40.34, Becton Dickinson) was also administered.…”
Section: Intravital Analysis Of Platelet Accumulation and Activation mentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanistically, the ability of AnxA5 to form two-dimensional crystal lattices on phosphatidylserine-rich membranes in a Ca 2+ -dependent manner in vitro seems most relevant (van Genderen et al, 2008;Rand et al, 2010). Hence, the AnxA5 KO animals could become a suitable model to further investigate therapeutic approaches to prevent inappropriate thrombogenesis causing infertility by the antiphospholipid syndrome in humans (Rand et al, 2012).…”
Section: Anxa5 Ko Micementioning
confidence: 99%
“…A critical role has emerged for the procoagulant platelet subpopulation in regulating both normal hemostasis and pathological thrombus formation 1, 3. Indeed, we have previously demonstrated that PS exposure on activated platelets persists in vitro,13 and in vivo,14 and that blocking the procoagulant surface inhibits platelet‐mediated events in experimentally induced arterial thrombosis 15…”
Section: Introductionmentioning
confidence: 98%